Revealing the Hidden Technology by Means of an Overhead Crane - Padula, Fabrizio; Adamini, R.; Finzi, G.; Visioli, A. (2017)
© 2017 In this paper we show that an industrial-like overhead crane can be effectively employed to show the role of control in industrial automation systems and in everyday life. The devised experiments are particularly indicated for secondary school students who are in general not aware of the presence of control in engineering. The related educational activity consists of explaining the integration of mechanics, electronics, computer science and control in an automation system and then of making the student understand that the presence of an automatic controller can increase the performance with respect to a manual one. The approach has been tested with some classrooms and the results obtained with an assessment questionnaire have shown the effectiveness of the approach.